2013
DOI: 10.1093/heapol/czt098
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chinese primary care providers’ recruitment and retention: a discrete choice experiment

Abstract: In order to retain skilled primary care providers to work in CHOs, policymakers in China need to improve primary care providers' income, benefits and working conditions to fulfil their basic needs. Policymakers also need to invest in CHOs' infrastructure and strengthen training programmes for primary care providers in order to raise the community's confidence in the services provided by CHOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 25 publications
3
68
0
1
Order By: Relevance
“…Two of these studies also included online questionnaires [51, 70], although three studies used computer-assisted surveys on student populations in LMIC [45, 56, 77]. In LMIC, response rates were generally very high, with a mean of 83.2% (range 65.2% to 100%, the latter from a study set in China as reported by authors [60]), compared to 49.3% (16.8 – 65.0%) in HICs. Unsurprisingly, response rates were significantly lower for graduates (mean of 62.7%, range 16.8 – 100%) than for students (mean 84.1%, range 62.7 – 100%), underscoring the potential for distortion if results from these two subgroups are combined.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies also included online questionnaires [51, 70], although three studies used computer-assisted surveys on student populations in LMIC [45, 56, 77]. In LMIC, response rates were generally very high, with a mean of 83.2% (range 65.2% to 100%, the latter from a study set in China as reported by authors [60]), compared to 49.3% (16.8 – 65.0%) in HICs. Unsurprisingly, response rates were significantly lower for graduates (mean of 62.7%, range 16.8 – 100%) than for students (mean 84.1%, range 62.7 – 100%), underscoring the potential for distortion if results from these two subgroups are combined.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified that positive workplace experiences, working conditions, geographical location, personal factors such as proximity to family or friends 1‐4 and high‐quality working culture can influence speciality or job choice 3 and intentions to stay or quit medical training in medical graduates 1,5‐11 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the poor quality of primary care services in rural areas of China. One recent study found that most general practitioners working in primary health facilities do not have college education experience and had received only 2-3 years of medical training in China [42]. Another study employing standardized patients found that general practitioners working at village clinics were able to correctly treat presumptive cases of angina 61.00% of the time and dysentery 45.00% of the time [43].…”
Section: Discussionmentioning
confidence: 99%